Structural snapshot of a glycoside hydrolase family 8 endo‐β‐1, 4‐glucanase capturing the state after cleavage of the scissile bond. Issue 2 (24th January 2022) - Fujiwara, Takaaki; Fujishima, Ayumi; Nakamura, Yui; Tajima, Kenji; Yao, Min
Abstract : The structure of an endo‐β‐1, 4‐glucanase from the cellulose‐producing bacterium Enterobacter sp. CJF‐002 bound to cellooligosaccharide was determined. Abstract : Bacterial cellulose (BC), which is produced by bacteria, is a biodegradable and biocompatible natural resource. Because of its remarkable physicochemical properties, BC has attracted attention for the development and manufacture of biomedical and industrial materials. In the BC production system, the enzyme endo‐β‐1, 4‐glucanase, which belongs to glycoside hydrolase family 8 (GH8), acts as a cleaner by trimming disordered cellulose fibers to produce high‐quality BC. Understanding the molecular mechanism of the endo‐β‐1, 4‐glucanase would help in developing a reasonable biosynthesis of BC. Nevertheless, all of the steps in the reaction of this endo‐β‐1, 4‐glucanase are not clear. This study confirms the BC hydrolytic activity of the endo‐β‐1, 4‐glucanase from the BC‐producing bacterium Enterobacter sp. CJF‐002 ( Eb BcsZ) and reports crystal structures of Eb BcsZ. Unlike in previously reported GH8 endo‐β‐1, 4‐glucanase structures, here the base catalyst was mutated (D242A) and the structure of this mutant bound to cellooligosaccharide [ Eb BcsZ(D242A)CPT ] was analyzed. The Eb BcsZ(D242A)CPT structure showed two cellooligosaccharides individually bound to the plus and minus subsites of Eb BcsZ. The glucosyl unit in subsite −1 presented a distorted 5 S 1 conformation, a novel snapshot of a state immediately after scissile‐bond cleavage. In combination with previous studies, the reaction process of endo‐β‐1, 4‐glucanase is described and the β‐1, 4‐glucan‐trimming mechanism of Eb BcsZ is proposed. The Eb BcsZ(D242A)CPT structure also showed an additional β‐1, 4‐glucan binding site on the Eb BcsZ surface, which may help to accept the substrate.